Functional status in patients undergoing lung resection - Macounová, Petra; Bobčíková, Katka; Tomášková, Hana; Mitták, Marcel; Argalášová, Ľubica (Archives of medical science, 2024)
INTRODUCTION: This prospective study aimed to evaluate the functional status and risk factors in patients undergoing lung resection. METHODS: Functional status defined by the parameters of spirometry (VC, FVC, FEV1, FEV1/FVC) and whole-body plethysmography (TLC) examination was assessed before lung resection, at hospital discharge, 3 weeks after surgery, and 3 months after surgery. RESULTS: The sample comprised 24 participants who were observed from 5/2021 to 10/2022. The functional status worsened significantly after the surgery, but the lung function values improved over time. CONCLUSIONS: Lung functions dropped sharply after the surgery but improved over time.
Keywords: lung resection; whole-body plethysmography; functional status; spirometry